Clinical Feature, Therapy, Antimicrobial Resistance Gene Distribution, and Outcome of Nosocomial Meningitis Induced by Multidrug-Resistant Enterobacteriaceae—A Longitudinal Cohort Study From Two Neurosurgical Centers in Northern China - Zheng, Guanghui; Shi, Yijun; Cao, Yanfei; Qian, Lingye; Lv, Hong; Zhang, Lina; Zhang, Guojun (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives: This is a comparative cohort study to evaluate the mortality risk factors of patients with nosocomial meningitis (NM) induced by multi-drug resistance Enterobacteriaceae (MDRE) in China. Clinical feature, therapy, and resistance mechanism of MDRE was screened as well. Methods: MDRE-NM patients from 2 neurosurgical centers in China from 2014 to 2019 were involved in this study. Clinical features were extract from the medical record database of the two centers. Molecular microbiological resistance mechanism of each MDRE was tested, and a Kaplan-Meier survival analysis was constructed, and multivariable analyses were performed by a Cox-proportional hazard model. Results: 90 MDRE-NM patients were included in this study. Klebsiella pneumoniae occupied the highest proportion (51.11%, 46/90), 40 (44.44%) were meropenem-resistant. blaKPC (67.50%, 27/40) was the predominant carbapenem resistance gene. Multivariate Cox analysis showed that external ventricular drainage (EVD, hazard ratio (HR) 2.524, 95% confidence interval (CI) 1.101-5.787, P = 0.029) and Glasgow Coma Scale (GCS) ≤8 (HR 4.033, 95% CI 1.526-10.645, P = 0.005) were mortality risk factors of MDRE-NM. 90.0%, 94.4%, and 97.8% MDRE-NM patients received antibiotic prophylaxis (AP), antibiotic empirical therapy(AET), and antibiotic definitive therapy(ADT) Conclusions: NM caused by MDRE is an important sign of the failure of neurosurgery, and MDRE has multiple drug resistance genotypes, and EVD and GCS≤8 are independent mortality risk factors of MDRE NM, which deserves the attention of microbiologist and neurosurgical clinicians.